Catalisadores contendo espécies V2O5 ou VO2+ : atividade e seletividade na redução de NO com amônia - Lima Neto, Antonio Vieira (Universidade Federal de São Carlos, 2009)
The selective catalytic reduction of NOx with ammonia is the best technology available today to carry out the abatement of nitrogen oxide emissions in industrial gas effluents. Currently, vanadia-titania catalysts promoted with WO3 or MoO3 are the most active catalysts for the mentioned reaction. They show a very good catalytic stability for a long time. However, vanadia is also active in the oxidation of SO2 (a compound commonly found in industrial effluents) to SO3 this reaction is highly undesirable since SO3 reacts with water present at effluent gas and ammonia, producing sulfuric acid and ammonium sulfates, NH4HSO4 and (NH4)2SO4. The ammonium sulfates can deposit and accumulate themselves on the catalyst surface besides causing pressure drop problems or equipment corrosion. Apart from this, vanadia-titania catalysts are partially sulfated in SO2 presence, they have specific surface area relatively low (in the order of 40 m2/g) and they can show difficulties when they are discarded because vanadia (as well as WO3 and MoO3) is poisonous to the soil and water. Thus, the optimization or search for new catalytic systems for the selective reduction of NOx with ammonia acquires a significative importance. For this reason, the present work was set in the context of technological route of the selective catalytic reduction of NOx with ammonia and it has the objective of investigate the performance of some catalysts and/or supports (zeolites, mesoporous molecular sieves and transition metal oxides) in the reaction in focus. The studied catalysts were prepared through incipient wet impregnation method or by ionic exchange between a support and a VOSO4 solution. Afterwards, the solids were analyzed by a number of characterization techniques and they were tested in the selective catalytic reduction of NOx with ammonia in the presence of oxygen, in a temperature range of 200°C to 500°C. The materials that have shown the best performances in this first test were subjected to stability tests with water and SO2. The results demonstrated that the Si/Al ratio and the molecular sieve structure, as well as the original cation nature to be exchanged, had influence on the catalyst behavior in the face of the reaction in focus. Finally, accordingly to the test battery accomplished in this investigation, one can say that zeolite H-ZSM-5 exchanged with VO2+ ion was the best catalyst to the selective catalytic reduction of NOx with ammonia, in the temperature range of 350°C to 500°C. It was better, in the test conditions, than the V2O5-WO3/TiO2 (similar to a commercial type).
Keywords: Catálise; Redução de NO; Amônia; Zeólita; Vanadila; Peneiras moleculares; ENGENHARIAS::ENGENHARIA QUIMICA